2020
DOI: 10.1002/jcp.29944
|View full text |Cite
|
Sign up to set email alerts
|

MRP8/14 mediates macrophage efferocytosis through RAGE and Gas6/MFG‐E8, and induces polarization via TLR4‐dependent pathway

Abstract: Myeloid-related protein 8/14 (MRP8/14) participates in various inflammatory responses, however, its effect on macrophage efferocytosis remains unclear. Here, we demonstrate that MRP8/14 significantly inhibits the efferocytosis of apoptotic thymocytes by mouse bone marrow-derived macrophages (BMDMs), which later proves to be associated with the receptor for advanced glycation end products (RAGE) or for reducing the expression of growth arrest-specific protein 6 and milk fat globule epidermal growth factor 8, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Diabetic wounds produce various inflammatory factors and chemotactic factors in the wound microenvironment, such as AGE, MCP-1, DAMPs, and IL-1β, which mutually induce the NLRP3 and IL-1R1 signaling pathways. These events impede macrophage polarization and directly affect the process of the efferocytosis function [30,31]. This study identified and validated that PROS1 may be a crucial gene influencing the macrophage efferocytosis phenotype in DFU.…”
Section: Discussionmentioning
confidence: 58%
“…Diabetic wounds produce various inflammatory factors and chemotactic factors in the wound microenvironment, such as AGE, MCP-1, DAMPs, and IL-1β, which mutually induce the NLRP3 and IL-1R1 signaling pathways. These events impede macrophage polarization and directly affect the process of the efferocytosis function [30,31]. This study identified and validated that PROS1 may be a crucial gene influencing the macrophage efferocytosis phenotype in DFU.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, glycosaminoglycans (GAGs) and EMMPRIN (CD147) were shown to be potential receptors for S100A8/A9 in melanoma cells [51,52]. However, data con rming the functional relevance of this interaction in C. albicans keratitis are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse MRP8/14 heterodimer and EGFP were prepared as described [ 17 , 27 ]. Endotoxin contaminants were removed using the Detoxi-Gel™ endotoxin removing gel, and the final endotoxin contaminants in the MRP8/14 heterodimer or EGFP preparations were confirmed by a Limulus amebocyte lysate assay (minimum LPS sensitivity = 0.125 EU/ml).…”
Section: Methodsmentioning
confidence: 99%